Correction: Study Protocol for 'PsilOCD: A Pharmacological Challenge Study Evaluating the Effects of the 5-HT2A Agonist Psilocybin on the Neurocognitive and Clinical Correlates of Compulsivity'. - O'Connor,S; Godfrey,K; Reed,S; Peill,J; Rohani-Shukla,C; Healy,M; Robbins,T; Frota,Lisboa Pereira de Souza A; Tyacke,R; Papasyrou,M; Stenbæk,D; Castro-Rodrigues,P; et al. (Cureus, 2025)
[This corrects the article DOI: 10.7759/cureus.78171.].